Broadening Pre-Service English Language Teachers’ Perceptions of Differentiation Relying on the 5D Model - Roiha Anssi (Routledge, Taylor & Francis Group, 2022)
Differentiation has gained increasing attention in contemporary pedagogy as an approach to cater for student diversity. However, particularly novice and pre-service teachers seem to struggle with applying it in practice. The aim of this study was to increase pre-service English teachers’ understanding of differentiation in Finland. Differentiation was approached through the 5-Dimensional (5 D) model of differentiation created by the author (e.g., Roiha & Polso, 2021b). The data of the study are 14 students’ learning journals written at the end of the course in which they reflected on the course content. The data were analyzed following thematic analysis. The findings showed that some students had formed a fairly progressive and wide understanding of differentiation whereas others still perceived it in a more restricted way. While almost all students regarded differentiation as highly important, many voiced several challenges for its effective implementation. Overall, the findings of this study imply that although the 5 D model had provided the students with a basic understanding of differentiation, many students still viewed differentiation predominantly through teaching methods. Therefore, it would be important in the future to emphasize other dimensions of the model, such as assessment or learning environment, to expand students’ perceptions of differentiation even more.